MENINGKATKAN KEMAMPUAN MENGENAL BANGUN DATAR SEDERHANA MELALUI CAI (Computer Assisted Instruction) PADA ANAK TUNAGRAHITA RINGAN (Single Subjeck research di SLB MuhammadiyahPauh IX Padang). - Merisa - Weni (Jurnal Penelitian Pendidikan Khusus, 2013)
This research of background overshadow by problems which is researcher find in field that is at a child of intelegance below of class III/C experiencing of resistance recognize to wake up to level off modestly. From result experiencing of child asesmen of trouble in activity of school like : recognizing to wake up to level off like is trilateral, parallelogram, square, and square of length. For that researcher cope to assist to improve ability recognize to wake up to level off child through CAI ( Computer Assisted Instruction ). This research owning target to prove that CAI ( Computer Assisted Instruction) can improve ability recognize to wake up to level off child of intelegance of class III/C SLB Muhammadiyah Pauh IX Padang. This type research is Single Subject Research (SSR) with reason of single accurate child or one. Stages steps usage of this SSR is conducted different to a condition use A-B desain. where condition of A is baseline namely the condition of early ability of child in recognizing to wake up to level off before given by action. While condition of B represent the condition of intervention namely the condition of where child given by intervention through CAI ( Computer Assisted Instruction). Result of this research, seen that ability recognize to wake up to level off child of intelegance below  of class III/C SLB Muhammadiyah Pauh IX Padang is mount after given by service through CAI ( Computer Assisted Instruction ). This proven Matter when perception performed within two session that is first of session baseline before given by intervention (A) which is conducted the five of perception times rill and percentage of ability recognize to wake up to level off at this condition lay in to span 0%,0%,0%,0% and 0%. Both, intervention session (B) by using CAI ( Computer Assisted Instruction ), perception conducted by counted eight times perception, and percentage of ability recognize to wake up to level off child of intelegance below at this condition lay in to span, 18,75%. 43,75%, 50%, 62,5%, 75%,81, 25%, 81,25%, 81,25%. Persuant to result of this research can mean that ability recognize to wake up to level off modestly child of intelekegance below of class III/C SLB Muhammadiyah Pauh IX Padang can mount to through CAI ( Computer Assisted Instruction ).